2011
DOI: 10.1021/jf200040z
|View full text |Cite
|
Sign up to set email alerts
|

Solar UV-B and ABA Are Involved in Phenol Metabolism of Vitis vinifera L. Increasing Biosynthesis of Berry Skin Polyphenols

Abstract: It has been previously found that abscisic acid (ABA) participates in the activation of grapevine leaf tissue defense against potentially damaging effects of solar ultraviolet-B radiation (UV-B), apparently by triggering biosynthesis of phenols that filter the harmful radiation and act as antioxidants. The present work studies the effect of solar UV-B and exogenously applied ABA on berry growth, sugar accumulation, and phenol (anthocyanin and nonanthocyanin) profiles across berry development and ripening of Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
153
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(173 citation statements)
references
References 40 publications
17
153
3
Order By: Relevance
“…In terms of a particular cultivar, the accumulation of phenolic compounds depends largely on the terroir, such as vineyard soil, topography and climate (Gladstones, 2011). Vineyard altitude could result in variations in temperature, solar radiation and ultraviolet radiation, and these climate factors have been demonstrated to have a strong effect on the synthesis of phenolic compounds (Mateus et al, 2001;Berli et al, 2011). Studies have also examined the effects of vineyard altitude on phenolic and aromatic compounds in grapes and the wines produced (Mateus et al, 2001;Berli et al, 2013), but so far these studies have been concerned mainly with oceanic climate conditions such as the North European (like Portugal) and South American (such as Brazil and Argentina) climates.…”
Section: Flavonoids In Grape Berries Grown On Highlandmentioning
confidence: 99%
“…In terms of a particular cultivar, the accumulation of phenolic compounds depends largely on the terroir, such as vineyard soil, topography and climate (Gladstones, 2011). Vineyard altitude could result in variations in temperature, solar radiation and ultraviolet radiation, and these climate factors have been demonstrated to have a strong effect on the synthesis of phenolic compounds (Mateus et al, 2001;Berli et al, 2011). Studies have also examined the effects of vineyard altitude on phenolic and aromatic compounds in grapes and the wines produced (Mateus et al, 2001;Berli et al, 2013), but so far these studies have been concerned mainly with oceanic climate conditions such as the North European (like Portugal) and South American (such as Brazil and Argentina) climates.…”
Section: Flavonoids In Grape Berries Grown On Highlandmentioning
confidence: 99%
“…Many factors such as grape variety, edaphoclimatic conditions and cultural and technological practices, may influence the phenolic composition of wines (Cynkar et al 2009;Obreque-Slier et al 2010;Puértolas et al 2010;Meng et al 2013). It has been reported that rain-shelter cultivation effectively delayed the maturation of grapes (Berli et al 2011;Meng et al 2013), slowed sugar accumulation by reducing photosynthetically active radiation (PAR) (Chavarria et al 2008;Chavarria et al 2009;Conceição & Marin 2009), increased berry and cluster weight, and improved economic returns (Tangolar et al 2007). During the several last decades, although rain-shelter cultivation has been studied for its commercial value on table grapes and other fruits (Fanizza & Ricciardi 1991;Tangolar et al 2007;Chavarria et al 2011;Pedro Júnior et al 2011), few studies have focused on wine grapes and wine.…”
mentioning
confidence: 99%
“…Higher PAR and daytime temperatures in Pinihue location may explain higher Brix values of severely defoliated vines (Song et al, 2015). However, no known reason can explain why T1 showed higher TA than the control treatment since changes in radiation and temperature are not generally related to increases in TA (Berli et al, 2011).…”
Section: Fruit Maturitymentioning
confidence: 94%